ANALISIS MOTIVASI BELAJAR SISWA PADA MASA PANDEMI COVID-19 DI LINGKUNGAN SOSORGADONG - Roslian Lubis; Tamin Ritonga; Donpipin Simatupang (JURNAL MathEdu (Mathematic Education Journal), 2022)
Abstract Learning motivation is a factor that has a lot of influence on students’ achievement. Changes in the education world in the Covid -19 pandemic are still being felt today. This situation provides opportunities for students to play in learning and causes their learning motivation to decrease. The aim of the research is to describe learning motivation of students in Sosorgadong environment. The approach of the research used qualitative descriptive by using questionnaire (Guttman scale) and interview (students and parents as the informant) in collecting the data. The result of the research 1) based on the interview with the students and parents, learning motivation is less and 2) based on questionnaire shows the average of learning motivation is 60 (less category). It’s concluded learning motivation of students in Sosorgadong environment in the Covid -19 pandemic is less.